Phage PPPL-1, A New Biological Agent to Control Bacterial Canker Caused by Pseudomonas syringae pv. actinidiae in Kiwifruit - Yu-Rim Song; Nguyen Trung Vu; Jungkum Park; In Sun Hwang; Hyeon-Ju Jeong; Youn-Sup Cho; Chang-Sik Oh (Antibiotics, 2021)
Pseudomonas syringae pv. actinidiae (Psa) is a Gram-negative bacterium that causes bacterial canker disease in kiwifruit. Copper or antibiotics have been used in orchards to control this disease, but the recent emergence of antibiotic-resistant Psa has called for the development of a new control agent. We previously reported that the bacteriophage (or phage) PPPL-1 showed antibacterial activity for both biovar 2 and 3 of Psa. To investigate the possibility of PPPL-1 to control bacterial canker in kiwifruit, we further tested the efficacy of PPPL-1 and its phage cocktail with two other phages on suppressing disease development under greenhouse conditions using 6 weeks old kiwifruit plants. Our results showed that the disease control efficacy of PPPL-1 treatment was statistically similar to those of phage cocktail treatment or AgrimycinTM, which contains streptomycin and oxytetracycline antibiotics as active ingredients. Moreover, PPPL-1 could successfully kill streptomycin-resistant Psa isolates, of which the treatment of BuramycinTM carrying only streptomycin as an active ingredient had no effect in vitro. The phage PPPL-1 was further characterized, and stability assays showed that the phage was stable in the field soil and at low temperature of 0 ± 2 °C. In addition, the phage could be scaled up quickly up to 1010 pfu/mL at 12 h later from initial multiplicity of infection of 0.000005. Our results indicate that PPPL-1 phage is a useful candidate as a biocontrol agent and could be a tool to control the bacterial canker in kiwifruit by Psa infection in the field conditions.